Physiological analysis of growth and yield of potato in relation to planting date - Begum, Farida; Kundu, BC; Hossain, MI (Journal of Bangladesh Academy of Sciences, 2015)
Experiments on planting date on growth and yield of potato revealed that planting date had a significant effect on plant height, crop growth and yield. Higher leaf area index (LAI) was observed in case of optimum sowing date (16 Nov.) which resulted in higher total dry matter (TDM) production and ultimately gave higher yield. Delayed planting gave lower LAI, lower TDM and had adverse effect on tuber yield. No significant variation was observed in tuber yield due to interaction effect of variety and planting date. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 45-51, 2015